Effect of binder variations on the performance of one-phase induction motors in bio-pellet production process - Ediwan Ediwan; Arnawan Hasibuan; Abubakar Dabet; Muhammad Daud; Fajar Syahbakti Lukman; Gandi Supriadi (International Journal of Advances in Applied Sciences, 2026)
Indonesia has many oil palm plantation areas. One of the negative impacts is the large amount of empty fruit bunch (EFB) waste. Utilizing EFB as a bio pellet as a renewable energy source is one of the solutions to reduce waste while supporting the green energy transition. EFB bio-pellets have the potential to replace fossil fuels, but face challenges in setting good quality standards. The production process of EFB bio-pellets uses a variety of binder contents. This study aims to analyze the influence of different levels of binder content on the quality of bio-pellet products. Statistical analysis of linear regression was performed to measure energy consumption and motor performance in the production process of EFB bio-pellets. This study provides recommendations to help maximize the quality and efficiency of the bio-pellet production process from palm oil EFB waste.